The Role of Family and Social Support in Maintaining the Health and Independence of Elderly People - Rahmat Israt; Riska Amalia Basri; Santuso (Generasi Sains Indonesia, 2026)
This study explores the relationship between family and social support and the health and independence of older people. The research will focus on the analysis of the relationships between emotional support, instrumental help and social integration in the context of functional autonomy and well-being of older people. Using the mixed methods approach, the study combined both qualitative interviews and quantitative surveys with 150 elderly participants (60 years and older). Both quantitative and qualitative data were analyzed and used to explore the experiences of support and independence for the elderly, with descriptive statistics applied to quantitative data and thematic analysis applied to the qualitative data. The results indicate that instrumental support and social participation are important predictors of elderly independence, and emotional support is the most important. Older adults who were actively engaged in community activities and had high levels of familial support had higher functional independence, psychological well-being, and life satisfaction. The qualitative results also suggest that a balance of care, emotional support and purposeful social engagement can aid to enhance dignity and autonomy in elderly age. It is quite unique in its holistic approach to family support and social participation as linked factors influencing healthy ageing. The results have implications for policy makers, health professionals, and families in formulating family-oriented and community-based approaches to support the elderly to retain independence, minimize social isolation, and enhance the quality of life for elderly people.